Inovasi agens hayati sebagai upaya peningkatan ekonomi petani di Desa Mojolegi Kecamatan Gading Kabupaten Probolinggo - Febrianto, Achmad; Andila, Ayu (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
The application of innovative biological agents to improve the agricultural economy in Mojolegi Village, Gading District, Probolinggo Regency, has been a breakthrough since last August 2015. This application is one way for farmers to overcome the high cost of synthetic fertilizers and prevent the adverse effects that synthetic chemicals will cause. Adverse effects will occur on yields and agricultural land in the excessive use of synthetic peptides in the long term. This research aims to find out the application of this biological agent innovation as a pioneer or initial bridge in Mojolegi Village. The method used is a qualitative method, namely a method that prioritizes research data to find results from the field using this research method through an interview system, as well as direct field observations, which are then collected as research material. As well as directly conducting interviews with the chief farmer, namely Mr Gatot Suprianto together with residents from research in Mojolegi village, the results included the influence of biological agent innovations on the economy of farmers in Mojolegi village, application and creation of biological agents in Mojolegi village, views of Mojolegi village farmers in the beginning natural agent innovation.